Method development of organization and planning monitoring for regional gas supply - Шевченко, Мария Валерьевна (Technology audit and production reserves, 2016)
In connection with the obsolescence of the gas supply equipment and increasing the volume of leaks in the gas pipelines, the problem of monitoring for regional gas supply at the moment is becoming more urgent. An analysis of previous studies in the article were identified outstanding issues in the problems of monitoring for regional gas supply system, formulated the aim of article and the basic objectives of the study. Important steps that precede the process of synthesis of the monitoring system for regional gas supply are the organization and planning monitoring. Each of these steps can be decomposed, and the results obtained at the upper levels, will be the source data for the lower levels. The research allowed developing a method of organization and planning monitoring, highlighting the basic steps in solving problems of organization and planning monitoring for regional gas supply. Based on earlier models of organization and planning at every stage of this method it is proposed to use a scheme of compromise or procedure max-min composition. This allows developers to make decisions under multicriteriality and fuzzy of initial data.